2020
DOI: 10.1177/0300060520920996
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia and opioid use following hip arthroscopy with ultrasound-guided quadratus lumborum block: a randomized controlled double-blind trial

Abstract: Objective To investigate the postoperative analgesic effect of ultrasound-guided quadratus lumborum block (QLB) in patients undergoing arthroscopic hip surgery. Methods Patients who were scheduled to undergo elective arthroscopic hip surgery were randomly assigned to the QLB (Q) or control (C) group (n = 40 each). After general anesthesia induction, unilateral QLB was performed under ultrasound guidance in the Q group. The amount of opioid use via patient-controlled analgesia (PCA) and the resting and movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…The use of peripheral nerve blocks has improved post-operative pain, lessened the use of opioids and their potential side effects, and decreased the incidence of sleep disturbance in patients (50). The use of quadratus lumborum blocks have shown mixed results in studies, but that could have been owed to the difference in the amount of local anesthetic used (51). The studies also noted that hydrodissection was not used in some studies examining the quadratus lumborum block so the block may not have spread enough to have appropriate effect.…”
Section: Discussionmentioning
confidence: 99%
“…The use of peripheral nerve blocks has improved post-operative pain, lessened the use of opioids and their potential side effects, and decreased the incidence of sleep disturbance in patients (50). The use of quadratus lumborum blocks have shown mixed results in studies, but that could have been owed to the difference in the amount of local anesthetic used (51). The studies also noted that hydrodissection was not used in some studies examining the quadratus lumborum block so the block may not have spread enough to have appropriate effect.…”
Section: Discussionmentioning
confidence: 99%
“…McCrum et al demonstrated in their cohort of patients who received a QL block had improved post-operative VAS scores versus those who received multimodal oral/intravenous medication [ 12 ]. Yuan et al also found that subjects who received a QL block had lower VAS pain scores in the PACU and within the first 24 h post-operatively when compared with a control group [ 13 ]. In this study, mean overall PACU VAS score (4.0 ± 2.0) in patients treated using our multimodal pain protocol was lower when compared with a recent systematic review examining 17 studies reporting on perioperative pain control following hip arthroscopy, which reported a mean PACU VAS score of 4.79 ± 2.04 [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the current multimodal pain regimen, greater opioid consumptions has been reported in studies utilizing the following modalities: PNB and preoperative non-narcotic medications [ 6 , 22 ], PNB and intraoperative local injection analgesia [ 16 , 23 ], pre-operative non-narcotic medications and local injection analgesia [ 2 ], and preoperative non-narcotic medications, intraoperative local injection analgesia with optional PNB post-operatively [ 21 ]. Furthermore, two recent studies have shown decreased total post-operative Meq in patients who have received a QL peripheral nerve block when compared to control group receiving traditional post-operative PO and IV pain medication [ 12 , 13 ]. These findings further emphasize the need for a pain control protocol that involves treatment during all three phases of care in the perioperative period in order to minimize post-operative opioid consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen articles were selected for full-text analysis. Of them, thirteen studies fulfilled the inclusion criteria and were analyzed in this review (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Details Of Included Studiesmentioning
confidence: 99%
“…Details of the included studies are presented in Table 1. Nine (21,24,26,(28)(29)(30)(31)(32)(33) were RCTs while four (22,23,25,27) were retrospective studies. Most studies were carried out in the USA or China.…”
Section: Details Of Included Studiesmentioning
confidence: 99%